Towards Re-usable Real-Time Objects - Nielsen, Brian; Agha, Gul (BRICS Report Series, 1998)
Large and complex real-time systems can benefit significantly from a component-based development approach where new systems are constructed by composing reusable, documented and previously tested concurrent objects. However, reusing objects which execute under real-time constraints is problematic because application specific time and synchronization constraints are often embedded in the internals of these objects. The tight coupling of functionality and real-time constraints makes objects interdependent, and as a result difficult to reuse in another system. We propose a model which facilitates separate and modular specification of real-time constraints, and show how separation of real-time constraints and functional behavior is possible. We present our ideas using the Actor model to represent untimed objects, and the Real-time Synchronizers language to express real-time and synchronization constraints. We discuss specific mechanisms by which Real-time Synchronizers can govern the interaction and execution of untimed objects. We treat our model formally, and succinctly define what effect real-time constraints have on a set of concurrent objects. We briefly discuss how a middleware scheduling and event-dispatching service can use the synchronizers to execute the system.